2001
DOI: 10.1080/13645700152601405
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal laparoscopic pyelolithotomy: how does it compare with percutaneous nephrolithotomy for larger stones?

Abstract: Our 10-year experience of retroperitoneal laparoscopic pyelolithotomy, a rarely performed minimally invasive operative procedure, is presented. The results are compared with our own experience of percutaneous nephrolithotomy for larger renal stones. Forty-two patients with a mean age of 39.12 years underwent 43 retroperitoneal laparoscopic pyelolithotomies using Gaur's balloon technique. The total number of stones was 65 (44 pelvic and 21 calyceal) and they ranged in size between 5 and 48 mm. Two patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Other stent-related complications encountered in the study were dysuria in 18.8% and minor hematuria in 6.2% of cases in group A. [3,6,9,10]. Complication rates in our study were comparable to other published studies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Other stent-related complications encountered in the study were dysuria in 18.8% and minor hematuria in 6.2% of cases in group A. [3,6,9,10]. Complication rates in our study were comparable to other published studies.…”
Section: Discussionsupporting
confidence: 80%
“…In 15.4% of patients with intrarenal pelvis, suturing of pyelotomy could not be performed. In other studies, patients with intrarenal pelvis also have been included as part of the study group, but they have not mentioned the implications of intrarenal pelvis on urinary leakage (Gaur et al (15/43 cases), Chander et al (9/56 cases)) [6,9]. Because closure of pyelotomy has been reported variably in different studies, it can be concluded that the ability to close pyelotomy laparoscopically depends on the operating surgeon's experience with endosuturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age difference between the groups was not statistically significant (p>0.05). Gaur, Pujani et al [7] reported a similar age distribution in their study, with a mean of 39.12 years. Jagdish Chander et al [12] reported a mean age of 33.74 years (18-60 yrs) in the group used in their study.…”
Section: Discussionmentioning
confidence: 50%
“…Micali Moore et al [4] reported a conversion rate of 11.76% (2/17) in their study. Similarly, Gaur et al 7 (2001) reported a conversion rate of 16.3% (7/43) in their study.…”
Section: Conversion Ratementioning
confidence: 94%